Activated carbon loaded platinum-cobalt alloy catalyst as well as preparation method and application thereof

Platinum-cobalt alloy nanoparticles were synthesized by solvent thermal reduction method, and the amino functional groups of activated carbon were enhanced by high-temperature activation treatment, solving the problem of catalyst particle size and uniformity, and achieving the effect of efficient catalyzing of VOCs gas.

CN119386894AActive Publication Date: 2025-02-07CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411517915.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The existing platinum-cobalt alloy catalysts have the problem that the particle size cannot be taken into account both the size and uniformity in the process of catalyzing VOCs gas, and there is a lack of synergistic effects between the support and nanometal particles, which affects the catalytic activity and stability.

Method used

Platinum-cobalt alloy nanoparticles were synthesized by solvent thermal reduction method, and the biomass activated carbon was subjected to high-temperature activation treatment to increase the amino functional groups on its surface, thereby forming a synergistic catalyst.

Benefits of technology

The high specific surface area and developed pore structure of the platinum-cobalt alloy catalyst are achieved, which inhibits the agglomeration of nanoparticles, improves catalytic activity and stability, and can efficiently catalyze the VOCs gas under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386894A_ABST
    Figure CN119386894A_ABST
Patent Text Reader

Abstract

The invention discloses an activated carbon loaded platinum-cobalt alloy catalyst and a preparation method and application thereof.The method comprises the steps that biomass raw materials are carbonized and then subjected to acid pickling impurity removal and high-temperature activation treatment under the action of an ammonia activator in sequence, and activated carbon is obtained; a solution containing a cobalt source, oleic acid, oleylamine and a reducing agent is mixed and dewatered, then a platinum source and o-dichlorobenzene are added for a solvothermal reduction reaction, and platinum-cobalt alloy nanoparticles are obtained; the activated carbon and the platinum-cobalt alloy nanoparticles are subjected to ultrasonic mixing, and the composite material is obtained. The process is simple, the cost is low, and the obtained catalyst is uniform in size, high in catalytic activity and excellent in catalytic conversion of volatile organic compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic nanomaterial chemistry and energy environment technology, and specifically relates to an activated carbon-supported platinum-cobalt alloy catalyst and a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) are a series of organic compounds with a boiling point of 50 to 250°C and are easily volatile at room temperature. They are listed as major air pollutants and are related to atmospheric environmental pollution, photochemical smog, etc., and most VOCs are irritating, toxic and carcinogenic to the human body. The indoor and outdoor emission sources of VOCs are very wide, including chemical industry, petroleum refining, papermaking, wood, carpets, etc. At present, the methods for treating VOCs include physical or chemical methods such as absorption, adsorption, membrane separation, condensation, combustion, catalytic oxidation and biocatalysis to control and purify the emission of VOCs. Among them, catalytic oxidation is to convert volatile organic compounds into less polluting compounds such as carbon dioxide and water. Compared with thermal oxidation, since the catalyst can reduce the activation energy of the reaction, the catalytic oxidation decomposition of VOCs can be achieved under the conditions of 250 to 500°C, which not only saves energy consumption under high temperature conditions and reduces the production of dioxins, but also can treat waste gas with low VOC content (concentration less than 1%).

[0003] VOCs oxidation catalysts can be roughly divided into three categories: precious metal catalysts, non-precious metal catalysts and mixed metal catalysts. However, these catalysts all have some shortcomings. Although precious metal catalysts such as platinum and palladium perform well in catalytic efficiency and stability, especially platinum-based catalysts have significant treatment effects on aromatic compounds, their high price and short service life limit their widespread application. Although non-precious metal catalysts such as manganese, cerium, and iron have cost advantages and good anti-toxicity, their catalytic activity and selectivity are often lower than those of precious metal catalysts, which may affect the efficiency and thoroughness of VOCs treatment. Although mixed metal catalysts such as Pd-Au and Mn-Co show better catalytic performance, their preparation process is usually more complicated and requires precise control of the metal ratio and distribution, which increases the difficulty and cost of catalyst preparation. In addition, the choice of catalyst carrier also has a significant impact on the catalytic effect. Although the existing porous materials have high specific surface area and rich pore size structure, the carrier fails to produce synergistic effects with the active center of nanometal particles, further improve the reaction active center, and reduce the reaction activation energy. Therefore, there are still certain limitations in the ability to protect the active sites of the catalyst in long-term use. At the same time, the particle size of the catalyst in the existing preparation method for platinum-cobalt alloy catalyst cannot take into account the problems of size and uniformity, and the nano-metal particles are prone to agglomeration during the loading process. Summary of the invention

[0004] In view of the shortcomings of platinum-cobalt alloy catalysts in the prior art, the first object of the present invention is to provide a method for preparing an activated carbon-supported platinum-cobalt alloy catalyst. The method uses a simple solvent thermal reduction method to effectively control the particle size of the platinum-cobalt alloy particles and prevent agglomeration between the particles through the ligand pair of oleic acid and oleylamine. At the same time, the biochar is activated to obtain rich amino functional groups on the surface of the activated carbon, thereby obtaining a catalyst in which the carrier and the platinum-cobalt alloy particles can synergistically improve the reaction active centers.

[0005] The second object of the present invention is to provide an activated carbon-supported platinum-cobalt alloy catalyst, which uses activated biomass activated carbon as a carrier, has a high specific surface area, developed pores, rich nitrogen-containing functional groups, uniformly supports platinum-cobalt alloy nanoparticles, and inhibits the agglomeration of particles. At the same time, the rich amino functional groups on the carrier can form more efficient reaction active centers with the supported platinum-cobalt alloy particles, and has high activity and high stability.

[0006] The third object of the present invention is to provide an application of an activated carbon-supported platinum-cobalt alloy catalyst, which is applied to the low-temperature catalytic oxidation of VOCs-containing exhaust gas. It has excellent catalytic oxidation ability and can efficiently catalytically oxidize and remove volatile organic compounds at a low temperature of 200°C, thereby reducing operating energy consumption.

[0007] In order to achieve the above technical objectives, the present invention provides a method for preparing an activated carbon-supported platinum-cobalt alloy catalyst, the method comprising the following steps:

[0008] 1) After the biomass raw material is carbonized, it is successively subjected to acid washing to remove impurities and high-temperature activation treatment under the action of an ammonia activator to obtain activated carbon;

[0009] 2) mixing a solution containing a cobalt source, oleic acid, oleylamine and a reducing agent, removing water, adding a platinum source and o-dichlorobenzene to carry out a solvent thermal reduction reaction to obtain platinum-cobalt alloy nanoparticles;

[0010] 3) The activated carbon and platinum-cobalt alloy nanoparticles are ultrasonically mixed to obtain the activated carbon.

[0011] The key to the technical solution of the present invention is to carry out high temperature activation treatment on the activated carbon after nitrogen high temperature carbonization, so that the activated carbon surface after activation has abundant amino functional groups, and then synthesize small-particle-size nano platinum-cobalt alloy particles by solvent thermal reduction method, load them on the activated carbon surface after activation, and obtain the activated carbon-loaded platinum-cobalt alloy catalyst with high specific surface area and developed pore structure. At the same time, the present invention introduces cobalt into the catalyst, reduces the use of precious metal platinum, reduces the production cost of the catalyst, and reasonably adds oleic acid, oleylamine and o-dichlorobenzene in the preparation of platinum-cobalt alloy nanoparticles, so that the metal atom platinum and metal atom cobalt after reduction can play a stabilizing role in alloying, help control particle size, prevent excessive growth and agglomeration, thereby forming platinum-cobalt alloy on a nanometer scale, and then improve the catalytic efficiency of the catalyst. In addition, the present invention carries out pickling and impurity removal between carbonization and high temperature activation treatment, which can remove various impurity elements (mainly various mineral ions) obtained from biomass carbon in activated carbon, eliminates the inhibitory effect of impurity elements, and ensures the stability of subsequent activation effect and catalytic performance.

[0012] The preparation principle of the cobalt-platinum alloy particles of the present invention is that: during the reaction process, the dibenzyl ether solvent provides a relatively stable medium for the solvent thermal reduction reaction, firstly, the residual water in the solvent is removed, and Ar gas is introduced to ensure that the reaction is carried out under anaerobic conditions to prevent oxidation of platinum and cobalt. Under the action of the oleylamine ligand, the platinum source and the cobalt source are formed into platinum-cobalt alloy nanoparticles by oleylamine and the reducing agent, and the oleic acid and oleylamine have a good regulating effect on the size of the platinum-cobalt nanoparticles.

[0013] The inventors have found that even if the biomass raw material is carbonized without being activated with an ammonia activator, the catalytic activity of the prepared composite material will be significantly reduced.

[0014] As a preferred solution, the biomass raw material is derived from cork oak bark, and in actual operation, corks or red wine corks can be selected.

[0015] As a preferred solution, the solution also includes benzyl ether solvent.

[0016] As a preferred solution, the carbonization conditions are: temperature of 700-1000°C, time of 1-4h, and nitrogen with a flow rate of 80-100mL / min as the protective atmosphere; the high-temperature activation treatment conditions are: temperature of 700-1000°C, time of 1-4h. The present invention can obtain a carrier with a high specific surface area and a high porosity structure by carbonization, which is beneficial to the loading of platinum-cobalt alloy particles, and by high-temperature activation in an ammonia activator and reaction etching with a porous carbon carrier, the activated activated carbon has a developed pore size and rich surface amino functional groups, which is beneficial to the adsorption and catalytic decomposition of volatile organic compound gases. The carbonization temperature affects the carbonization degree of biomass. Too high a carbonization temperature will increase the energy consumption of equipment operation, while a lower temperature will result in incomplete carbonization. The temperature of the high-temperature activation treatment has a direct impact on the adsorption performance of the carrier. Within the scope of the present invention, as the activation treatment temperature increases, the adsorption performance of the carrier becomes stronger. It is further preferred that the activation temperature is 800-1000°C.

[0017] As a preferred solution, during the high temperature activation treatment, the ammonia activator is ammonia gas and / or ammonia water. When the ammonia activator is ammonia gas, the flow rate of ammonia gas is 25-100 mL / min, and when the ammonia activator is ammonia water, the mass fraction of ammonia water is 5-25 wt%. In the present invention, ammonia gas and / or ammonia water are used as activators, so that the activated carbon surface can obtain abundant amino functional groups during the activation reaction etching process. The amino functional groups on the surface of the activated carbon can not only improve the dispersibility of the platinum-cobalt alloy nanoparticles, but also form more efficient reaction active centers with the platinum-cobalt alloy particles loaded on the surface, reduce the reaction activation energy, and thus improve its catalytic ability. The increase in the amount of ammonia activator can increase the amino functional group content on the surface of the activated carbon to a certain extent, increase the specific surface area, improve the pore structure, and thus facilitate the dispersion of the platinum-cobalt alloy nanoparticles and the catalytic reaction. However, the use of excessive ammonia activator will lead to excessive etching, which will reduce the specific surface area of ​​the activated carbon carrier, which is not conducive to the performance improvement of the catalyst, and the yield of the activated carbon will decrease. More preferably, the ammonia activating agent is ammonia gas at a flow rate of 50 to 100 mL / min.

[0018] As a preferred solution, the molar ratio of the cobalt source to the platinum source is (8-16): 1. In the present invention, the amount of the cobalt source is greater than that of the platinum source, which reduces the amount of precious metal platinum while ensuring the activity of the catalyst, thereby obtaining a low-platinum catalyst, which can reduce the production cost and use cost of the catalyst.

[0019] As a preferred solution, the cobalt source is one of cobalt acetylacetonate, cobalt chloride, cobalt nitrate and cobalt acetate; the platinum source is one of platinum acetylacetonate, chloroplatinic acid and diaminodinitroplatinum. It is further preferred that the cobalt source is cobalt acetylacetonate and the platinum source is platinum acetylacetonate.

[0020] As a preferred solution, the reducing agent is tetraphenyl dipropylene glycol diphosphite (TDD). The TDD reducing agent used in the present invention not only reduces the platinum source and the cobalt source into metal particles, but also has the function of a surfactant, which can improve the dispersibility of the particles.

[0021] As a preferred solution, the conditions of the solvent thermal reduction reaction are: temperature of 180-240°C and time of 30-90 minutes. The present invention controls the conditions of the reduction reaction during the preparation of platinum-cobalt alloy nanoparticles to control the size and uniformity of the platinum-cobalt alloy particles. Too high a temperature may cause the diffusion rate of metal atoms to be too fast, resulting in a fast formation speed and rapid growth of nanoparticles, resulting in an increase in the size of the particles and an uneven distribution of particle sizes, which will result in a decrease in the specific surface area of ​​the alloy nanoparticles, an irregular lattice structure, and a larger grain size. Too high a reduction temperature may also cause the metal to be thermally decomposed or oxidized, resulting in a decrease in the synthesis yield of the nanoparticles, or even failure to form alloy nanoparticles; while too low a temperature will reduce the reaction rate, slowing down the reduction and synthesis process of metal atoms, thereby increasing the formation time of the alloy nanoparticles. If the temperature is too low, the reduction reaction effect is poor, and cobalt ions and platinum ions are difficult to be reduced to form low-platinum alloy nanoparticles. During the reduction reaction, metal ions will be continuously reduced to metal atoms and continue to diffuse and grow grains. If the reduction time is too long, the size of the grains may increase, thereby reducing the specific surface area of ​​the nanoparticles, reducing their catalytic performance and active site density; if the reduction time is too short, the cobalt source and platinum source may not be completely reduced to metal atoms, resulting in residues in the product, affecting the composition and crystal structure of the alloy nanoparticles and reducing their catalytic performance. Too short a reduction time may also lead to poor dispersion of the alloy nanoparticles and uneven grain size distribution, affecting their catalytic activity and stability.

[0022] As a preferred solution, the mixed dehydration is heated in an argon environment at 80-120° C. for 30-90 minutes. In an argon environment, the reaction can be carried out in an oxygen-free condition to prevent oxidation of platinum and cobalt.

[0023] As a preferred solution, the ultrasonic mixing time is 10 to 60 minutes. Within the ultrasonic mixing time range of the present invention, the loading of platinum-cobalt alloy particles can be effectively achieved.

[0024] As a preferred solution, the volume ratio of oleic acid to oleylamine is (0.8-1.2):1, and the total amount of oleic acid and oleylamine relative to the amount of cobalt source is (0.2-1) L / mol. Oleic acid and oleylamine play an important role in the formation of platinum-cobalt alloy nanoparticles. The carboxyl group in oleic acid can react with platinum-cobalt metal ions to form a stable complex, and oleylamine has good reducibility, thereby obtaining platinum-cobalt nanoparticles through oleylamine reduction. In addition, the ligand pair of oleic acid and oleylamine can control the size and shape of platinum-cobalt alloy nanoparticles and prevent their aggregation.

[0025] The present invention provides a method for preparing an activated carbon-supported platinum-cobalt alloy catalyst, which specifically comprises the following steps:

[0026] 1) The biomass raw material is dried and crushed into powder particles, carbonized under nitrogen atmosphere to obtain carbonized material, the carbonized material is acid-washed to remove impurities, washed with water to neutrality, and dried to obtain biochar. The biochar is activated under high temperature conditions using an ammonia activator to obtain activated carbon.

[0027] 2) Dissolve the cobalt source, oleic acid, oleylamine and reducing agent in dibenzyl ether, heat for 30 to 90 minutes at 80 to 120°C in an argon environment to remove moisture from the system. Heat to 180 to 240°C, add the platinum source and o-dichlorobenzene, and keep warm for 30 to 90 minutes. Cool naturally to room temperature, add ethanol to a three-necked flask, and centrifuge at 10,000 rpm to obtain platinum-cobalt alloy particles.

[0028] 3) Place the activated carbon and platinum-cobalt alloy particles in n-hexane, perform ultrasonic treatment for 10 to 60 minutes, and dry in a vacuum drying oven at 40 to 60° C. to obtain a black powder, which is the activated carbon-supported platinum-cobalt alloy catalyst.

[0029] The present invention also provides an activated carbon-supported platinum-cobalt alloy catalyst, which has a nanometer-scale particle size, a high specific surface area and a developed pore structure, and exhibits excellent catalytic activity when catalyzing volatile organic compound gases.

[0030] As a preferred solution, the activated carbon-supported platinum-cobalt alloy catalyst has a honeycomb-like three-dimensional porous structure, and the activated carbon is uniformly loaded with platinum-cobalt alloy nanoparticles.

[0031] Finally, the present invention also provides an application of an activated carbon-supported platinum-cobalt alloy catalyst, which is used in the low-temperature catalytic oxidation of VOCs-containing waste gas. When the catalyst of the present invention is used in the low-temperature catalytic oxidation reaction of VOCs waste gas, it has good catalytic oxidation ability and can efficiently catalytically oxidize and remove volatile organic compounds at a low temperature of 200°C, thereby reducing operating energy consumption.

[0032] The principle that the catalyst of the present invention has a high catalytic ability for VOCs waste gas under low temperature conditions is that: on the one hand, the amino functional group enhances the adsorption effect of the catalyst on toluene, which is beneficial to the catalytic reaction process; on the other hand, the amino nitrogen functional group on the surface of the activated carbon interacts with the platinum-cobalt alloy nanoparticles, wherein the presence of the amino functional group adjusts the electronic structure of the platinum-cobalt alloy, reduces the activation energy of the catalytic oxidation reaction of toluene, and further optimizes the toluene catalytic reaction ability of the catalytic active center, thereby forming a high-efficiency reaction active center of the amino functional group-platinum-cobalt alloy.

[0033] As a preferred solution, the catalyst can be used in the reaction of converting toluene into CO2 at a temperature below 200°C. The amount of catalyst used in the reaction is less than 15000 h -1 Accounting.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1) The catalyst of the present invention uses activated biomass activated carbon as a carrier, has a high specific surface area, developed pores, rich nitrogen-containing functional groups, uniformly loads platinum-cobalt alloy nanoparticles, and inhibits the agglomeration of particles. At the same time, the rich amino functional groups on the carrier can form more efficient reaction active centers with the loaded platinum-cobalt alloy particles, and has high activity and high stability.

[0036] 2) The process flow of the present invention is simple, and the readily available biomass raw materials are used as carriers, which has high economic benefits. At the same time, the introduction of cobalt synthesizes low-platinum nanocatalysts, reduces the use of precious metal platinum, and reduces the production cost of the catalyst.

[0037] 3) The activated carbon-supported platinum-cobalt nanocatalyst synthesized in the present invention has excellent VOCs catalytic oxidation ability, realizes efficient catalytic oxidation removal of toluene under low temperature conditions, and can reduce operating energy consumption.

[0038] 4) The method of the present invention uses a simple solvent thermal reduction method to effectively control the particle size of the platinum-cobalt alloy particles and prevent agglomeration between the particles through the pairing of oleic acid and oleylamine, and at the same time activates the biochar so that the surface of the activated carbon obtains rich amino functional groups, thereby obtaining a catalyst in which the carrier and the platinum-cobalt alloy particles can synergistically improve the reaction active center. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a comparison chart of the adsorption capacity of toluene by the biochar C800 prepared in Example 1 and the catalyst carriers N700, N800 and N900.

[0040] Figure 2TEM images of catalyst supports NQ25 (a), NQ50 (b) and NQ100 (c) prepared in Example 2.

[0041] Figure 3 This is the SEM image of the catalyst carrier N900 prepared in Example 3.

[0042] Figure 4 TEM image of the platinum-cobalt alloy catalyst PtCo3@N900 prepared in Example 3.

[0043] Figure 5 This is the SEM image of biochar C800 prepared in Comparative Example 1.

[0044] Figure 6 This is the particle size distribution diagram of the platinum-cobalt alloy catalyst PtCo3 alloy nanoparticles prepared in Example 3.

[0045] Figure 7 This is the toluene catalytic oxidation conversion efficiency diagram of the platinum-cobalt alloy catalyst PtCo3@N900 prepared in Example 3.

[0046] Figure 8 This is the toluene catalytic oxidation conversion efficiency diagram of the catalyst PtCo3@C800 prepared in Comparative Example 1.

[0047] Fig. 9 This is the catalytic oxidation conversion efficiency diagram of toluene for catalysts PtCo3@NQ25, PtCo3@NQ50 and PtCo3@NQ100 prepared in Example 2. DETAILED DESCRIPTION

[0048] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by professionals in this field without creative work still belong to the protection scope of the present invention.

[0049] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0050] Example 1 (Activation temperature exploration experiment)

[0051] (1) Carbonization process:

[0052] The biomass raw material cork (made of cork oak) was dried and crushed into powder particles, and then carbonized at 800°C for 2 h in a nitrogen atmosphere of 100 mL / min to obtain a carbonized material. The carbonized material was acid-washed with HCl to remove impurities, washed with water to neutrality, and dried at 60°C to obtain biochar, named C800.

[0053] (2) Activation process:

[0054] The biochar C800 was activated with 100 mL / min NH3 at high temperatures of 700°C, 800°C and 900°C for 1 h, and then cooled to room temperature to obtain activated carbons, i.e., catalyst carriers, which were named N700, N800 and N900, respectively.

[0055] The toluene adsorption performance of C800, N700, N800 and N900 was tested at 25°C and 3kPa (the carrier dosage was 30g). The results are as follows: Figure 1 shown.

[0056] Depend on Figure 1 The results show that compared with the biochar carrier C800, the active carriers after ammonia activation have improved the adsorption capacity for toluene; and with the increase of activation temperature, the adsorption performance of the catalyst carrier also increases, among which N900 shows an outstanding toluene adsorption effect, which is due to the developed pore structure, large specific surface area and rich amino functional groups of N900. The activation temperature is further optimized to be 800-900℃.

[0057] Example 2 (Activator Dosage Exploration Experiment)

[0058] (1) Carbonization process:

[0059] The biomass raw material cork was dried and crushed into powder particles, and carbonized at 800°C for 2 h in a nitrogen atmosphere of 100 mL / min to obtain a carbonized material. The carbonized material was washed with HCl to remove impurities, washed with water to neutrality, and dried at 60°C to obtain biochar, named C800.

[0060] (2) Activation process:

[0061] The biochar C800 was activated at a high temperature of 900°C with NH3 at flow rates of 25 mL / min, 50 mL / min, and 100 mL / min for 1 h. After cooling to room temperature, activated carbons, i.e., catalyst carriers, were obtained, which were named NQ25, NQ50, and NQ100 (i.e., N900), respectively.

[0062] (3) Preparation of platinum-cobalt alloy nanoparticles:

[0063] In a three-necked flask, 1.16g of cobalt acetylacetonate, 0.4mL of oleic acid, 0.4mL of oleylamine and 200mg of reducing agent tetraphenyldipropylene glycol diphosphite (TDD) were dissolved in 30mL of dibenzyl ether. The air in the three-necked flask was purged with a 100mL / min argon gas flow, and heated at 100°C for 1h to remove the water in the solution. The three-necked flask was heated to 200°C, 0.2mmol of platinum acetylacetonate and 1.4mL of o-dichlorobenzene were added, and the temperature was kept for 1h. After cooling to room temperature, 50mL of anhydrous ethanol was added, and the platinum-cobalt alloy nanoparticles PtCo3 were obtained by centrifugation.

[0064] (4) Catalyst synthesis: PtCo3 nanoparticles and catalyst carriers NQ25, NQ50 and NQ100 (N900) were added to 30 mL of n-hexane and ultrasonically treated for 30 min to uniformly load the PtCo3 nanoparticles onto the biomass activated carbon carrier. After washing several times, the mixture was placed in a vacuum drying oven and dried at 60 °C for 18 h to obtain low-platinum catalysts PtCo3@NQ25, PtCo3@NQ50 and PtCo3@NQ100 (PtCo3@N900).

[0065] The catalyst carriers NQ25, NQ50 and NQ100 prepared in Example 2 were tested by transmission electron microscopy. The results are as follows: Figure 2 As shown. Figure 2 It shows that the micropore structure of the activated carbon surface is adjusted with the increase of the amount of activator.

[0066] Example 3

[0067] (1) Preparation of catalyst carrier:

[0068] The cork corks were dried and crushed into powders, and carbonized at 800℃ for 2h in a nitrogen atmosphere (nitrogen flow rate was 100mL / min) to obtain carbonized material. The carbonized material was washed with HCl to remove impurities, washed with water to neutrality, and dried at 60℃ to obtain biochar, named C800. Biochar C800 was activated at 900℃ with 100mL / min NH3 for 1h, and then cooled to room temperature to obtain activated carbon, i.e., catalyst carrier, named N900.

[0069] (2) Preparation of platinum-cobalt alloy nanoparticles:

[0070] In a three-necked flask, 1.16 g of cobalt acetylacetonate, 0.4 mL of oleic acid, 0.4 mL of oleylamine and 200 mg of reducing agent TDD were dissolved in 30 mL of dibenzyl ether. The air in the three-necked flask was purged with a 100 mL / min argon gas flow, and heated at 100 ° C for 1 hour in an argon environment to remove moisture from the solution. The three-necked flask was heated to 200 ° C, 0.2 mmol of platinum acetylacetonate and 1.4 mL of o-dichlorobenzene were added, and the temperature was kept for 1 hour. After cooling to room temperature, 50 mL of anhydrous ethanol was added, and the platinum-cobalt alloy nanoparticles PtCo3 were obtained by centrifugation. The particle size distribution of the platinum-cobalt alloy prepared by the present invention is shown in FIG. Figure 6 ,like Figure 6 As shown, the platinum-cobalt alloy prepared by the present invention has a small particle size and a narrow distribution, which is uniformly distributed in the range of 2 to 3 nm.

[0071] (3) Synthetic catalyst:

[0072] Nanoparticles PtCo3 and biomass activated carbon N900 were added to 30 mL of n-hexane and ultrasonically treated for 30 min to uniformly load the PtCo3 nanoparticles onto the biomass activated carbon carrier. After washing several times, the mixture was placed in a vacuum drying oven and dried at 60 ° C for 18 h to finally obtain the low-platinum catalyst PtCo3@N900.

[0073] At the same time, the N700 and N800 catalyst carriers prepared at 700°C and 800°C in Example 1 were loaded with the platinum-cobalt alloy nanoparticles prepared in this example under the same conditions to obtain PtCo3@N700 and PtCo3@N800, which also showed higher activity than the unactivated catalyst.

[0074] Comparative Example 1

[0075] (1) Preparation of catalyst carrier: The biomass raw material cork was dried and crushed into powder particles, and carbonized at 800 °C for 2 h in a nitrogen atmosphere with a flow rate of 100 mL / min to obtain a carbonized material. The carbonized material was washed with HCl to remove impurities, washed with water to neutrality, and dried at 60 °C to obtain biochar, named C800.

[0076] (2) Preparation of platinum-cobalt alloy nanoparticles: In a three-necked flask, 1.16 g of cobalt acetylacetonate, 0.4 mL of oleic acid, 0.4 mL of oleylamine and 200 mg of reducing agent TDD were dissolved in 30 mL of dibenzyl ether. The air in the three-necked flask was purged with a 100 mL / min argon gas flow, and heated at 100 ° C for 1 h in an argon environment to remove moisture from the solution. The three-necked flask was heated to 200 ° C, 0.2 mmol of platinum acetylacetonate and 1.4 mL of o-dichlorobenzene were added, and the temperature was kept for 1 h. After cooling to room temperature, 50 mL of anhydrous ethanol was added, and the platinum-cobalt alloy nanoparticles PtCo3 were obtained by centrifugation.

[0077] (3) Catalyst synthesis: PtCo3 nanoparticles and biomass activated carbon C800 were added to 30 mL of n-hexane and ultrasonically treated for 30 min to uniformly load the PtCo3 nanoparticles onto the biomass activated carbon carrier. After washing several times, the mixture was placed in a vacuum drying oven and dried at 60 °C for 18 h to obtain the low-platinum catalyst PtCo3@C800.

[0078] The activated catalyst carrier N900 prepared in Example 3 and the unactivated catalyst carrier C800 prepared in Comparative Example 1 were tested by scanning electron microscope. The results are as follows: Figure 3 and Figure 5 As shown, from Figure 5 It can be seen that the biomass after high temperature carbonization has a honeycomb-like porous structure. Figure 3 It can be seen that after high-temperature activation, it still maintains its unique honeycomb-like structure.

[0079] The activated carbon-supported platinum-cobalt alloy catalyst PtCo3@N900 prepared in Example 3 was tested by transmission electron microscopy. The results are as follows: Figure 4 ,Depend on Figure 4 It can be seen that the platinum-cobalt nanoparticles are uniformly loaded on the surface of the activated carbon carrier.

[0080] Catalyst activity evaluation

[0081] The catalytic oxidation effects of the low-platinum catalysts PtCo3@NQ25, PtCo3@NQ50 and PtCo3@NQ100 of Example 2, the low-platinum catalyst PtCo3@N900 of Example 3 and the catalyst prepared in Comparative Example 1 were evaluated as follows: the catalysts were mixed with an appropriate amount of quartz sand (30 mg of catalyst and 0.8 cm 3 The quartz sand) was mixed evenly and placed in the catalytic reaction container. In the catalyst catalytic activity experiment, the reaction gas with a total gas flow rate of 160mL / min was introduced, including: three toluene concentrations of 400, 700 and 1000ppm, 20% oxygen and nitrogen as the balance gas, and the gas hourly space velocity (GHSV) was 12000h -1 . Through the programmed temperature rising process, the concentration of toluene in the tail gas at each temperature is recorded, and the conversion rate of toluene is calculated (in the present invention, toluene is converted into CO2, which is calculated by the toluene concentration and CO2 content before and after the reaction. The concentrations of toluene and CO2 can be detected simultaneously by gas chromatography, and the toluene conversion rate can be calculated).

[0082] The conversion rate of toluene is shown in Figure 7 , Figure 8 and Fig. 9 , Figure 7This is a graph showing the catalytic oxidation conversion efficiency of toluene of the catalyst prepared in Example 3. It can be seen from the graph that toluene gradually begins to oxidize and decompose at 160°C under the action of the PtCo3@N900 catalyst, and the toluene conversion efficiency also increases with decreasing concentration. At 210°C, the conversion rate of toluene at all concentrations reaches more than 99%. Figure 8 The toluene catalytic oxidation conversion efficiency result diagram of the catalyst prepared in Comparative Example 1 is shown in FIG. Figure 8 It can be seen that under the action of PtCo3@C800 catalyst, toluene needs to start to be gradually oxidized and decomposed from 200°C, and the toluene conversion efficiency increases with the decrease of concentration. Fig. 9 Comparison of the catalytic performance of PtCo3@NQ25, PtCo3@NQ50 and PtCo3@NQ100 prepared in Example 2 (where the concentration of toluene is 1000 ppm), Fig. 9 It can be seen that the PtCo3@NQ100 catalyst exhibits the best catalytic effect on toluene, and gradually begins to oxidize and decompose from 160°C. At 205°C, the conversion rate of toluene reaches more than 99%. However, under the action of PtCo3@NQ50 and PtCo3@NQ25 catalysts, toluene needs to be gradually oxidized and decomposed from 180°C, and at 230°C, the conversion rate of toluene reaches more than 99%. The examples confirm the promoting effect of the activation of the catalyst carrier on the catalytic cracking of toluene, and more preferably 50-100 mL / min.

[0083] At the same time, the conversion temperatures of the catalysts at different toluene concentrations when converting 50% and 90% toluene are statistically analyzed, and the results are tabulated in Table 1. According to the data in Table 1, the toluene catalytic efficiency of the biomass activated carbon carrier catalyst PtCo3@N900 activated by ammonia is significantly better than that of the catalyst of the unactivated biomass carbon carrier. Thanks to the activated carrier and the excellent distribution characteristics of platinum cobalt nanoparticles, the PtCo3@N900 catalyst prepared in Example 3 has a toluene conversion efficiency of 90% at a concentration of 400ppm at only 193°C, and has higher catalytic activity.

[0084] Table 1 shows the T values ​​of the catalysts prepared in Example 3 and Comparative Example 1 at different toluene concentrations. 50 、T 90 Transformation temperature

[0085]

Claims

1. A method for preparing an activated carbon-supported platinum-cobalt alloy catalyst, characterized in that: The following steps are involved: 1) After the biomass raw material is carbonized, it is successively subjected to acid washing to remove impurities and high-temperature activation treatment under the action of an ammonia activator to obtain activated carbon; 2) mixing a solution containing a cobalt source, oleic acid, oleylamine and a reducing agent, removing water, adding a platinum source and o-dichlorobenzene to carry out a solvent thermal reduction reaction to obtain platinum-cobalt alloy nanoparticles; 3) The activated carbon and platinum-cobalt alloy nanoparticles are ultrasonically mixed to obtain the activated carbon.

2. The method for preparing an activated carbon-supported platinum-cobalt alloy catalyst according to claim 1, characterized in that: The carbonization conditions are: temperature of 700-1000°C, time of 1-4h, and nitrogen with a flow rate of 80-100mL / min as the protective atmosphere; the high-temperature activation treatment conditions are: temperature of 700-1000°C, time of 1-4h.

3. The method for preparing an activated carbon-supported platinum-cobalt alloy catalyst according to claim 1 or 2, characterized in that: During the high-temperature activation treatment, when the ammonia activator is ammonia gas, the flow rate of the ammonia gas is 25-100 mL / min; when the ammonia activator is ammonia water, the mass fraction of ammonia water is 5-25 wt %.

4. The method for preparing an activated carbon-supported platinum-cobalt alloy catalyst according to claim 1, characterized in that: The molar ratio of the cobalt source to the platinum source is (8-16):

1.

5. The method for preparing an activated carbon-supported platinum-cobalt alloy catalyst according to claim 1 or 4, characterized in that: The cobalt source is one of cobalt acetylacetonate, cobalt chloride, cobalt nitrate and cobalt acetate; The platinum source is one of acetylacetonate platinum, chloroplatinic acid and diaminodinitroplatinum; The reducing agent is tetraphenyl dipropylene glycol diphosphite.

6. The method for preparing an activated carbon-supported platinum-cobalt alloy catalyst according to claim 5, characterized in that: The conditions of the solvent thermal reduction reaction are: temperature of 180-240° C., time of 30-90 min; the mixed dehydration is heated in an argon environment at 80-120° C. for 30-90 min.

7. The method for preparing an activated carbon-supported platinum-cobalt alloy catalyst according to claim 1, characterized in that: The volume ratio of oleic acid to oleylamine is (0.8-1.2):1, and the total amount of oleic acid and oleylamine relative to the amount of cobalt source is (0.2-1) L / mol.

8. An activated carbon-supported platinum-cobalt alloy catalyst, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. The activated carbon-supported platinum-cobalt alloy catalyst according to claim 8, characterized in that: It has a honeycomb-like three-dimensional porous structure, and the activated carbon is uniformly loaded with platinum-cobalt alloy nanoparticles.

10. Use of an activated carbon-supported platinum-cobalt alloy catalyst according to claim 8 or 9, characterized in that: Applied to low-temperature catalytic oxidation of waste gas containing VOCs.

Citation Information

Patent Citations

  • Preparation method of noble metal-loaded active carbon material catalyst

    CN104307551A

  • Preparation method of platinum-cobalt alloy nano-catalyst and application of platinum-cobalt alloy nano-catalyst to oxygen reduction reaction

    CN107342426A

  • Preparation method and application of carbon-loaded platinum cobalt nanometer alloy catalyst

    CN108258251A

  • Method for producing platinum-cobalt alloy fine particle

    JP2011149042A

  • Ultra-small stable platinum-cobalt nanoparticle catalyst, and preparation method therefor and use thereof in selective hydrogenation

    WO2024109834A1